A semi-analytic method for vibro-acoustic analysis of coupled propeller-shaft-hull systems under propeller excitations - Xie, Kun; Chen, Meixia; Dong, Wanjing; Li, Wencheng (Ocean engineering, 2020)
A semi-analytic dynamic model is developed for vibro-acoustic analysis of submerged coupled propeller-shaft-hull systems under propeller forces. The propeller, shaft and hull are idealized as a lumped mass, multi-span beam and ring-stiffened shell of revolution, respectively. Stern, middle and thrust bearings are simulated as spring-damping systems. The hull is firstly decomposed into many segments, which are treated as conical shells and analyzed through combining Flügge shell theory and power series method. The shaft is divided into three Timoshenko beams according to the bearings. By expanding acoustic pressure and velocity as Fourier series in circumferential direction, surface Helmholtz integral equation is reduced to line integral, and acoustic pressure is further expressed as displacements of segments after meshing the line to some 3-node isoparameter elements. Boundary conditions and continuity conditions modified by external acoustic pressure are orderly assembled to the dynamic model. As considering the hull as a ring-stiffened conical-cylindrical-spherical shell, vibro-acoustic results of present method are compared with ones of coupled finite element-boundary element method, and the accuracy and efficiency of developed dynamic model are demonstrated. Furthermore, parameter analysis reveals that breathing and beam modes are predominant for vibro-acoustic responses, and sound power is mainly dominated by the cylindrical compartment. •A dynamic model for vibro-acoustics of coupled propeller-shaft-hull systems under propeller forces.•A more general model, ring-stiffened shells of revolution, is developed for the hull.•Present semi-analytic method is of wide application and high accuracy and efficiency.•Breathing and beam modes are mainly contributed to vibro-acoustic responses of the coupled system.